2011
DOI: 10.1016/s0140-6736(11)60783-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mobile phone text-message reminders on Kenyan health workers' adherence to malaria treatment guidelines: a cluster randomised trial

Abstract: SummaryBackgroundHealth workers' malaria case-management practices often differ from national guidelines. We assessed whether text-message reminders sent to health workers' mobile phones could improve and maintain their adherence to treatment guidelines for outpatient paediatric malaria in Kenya.MethodsFrom March 6, 2009, to May 31, 2010, we did a cluster-randomised controlled trial at 107 rural health facilities in 11 districts in coastal and western Kenya. With a computer-generated sequence, health facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
319
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(330 citation statements)
references
References 25 publications
6
319
3
2
Order By: Relevance
“…The advocated number for messages sent through SMS is 160. (22) For messages sent through WhatsApp, there is no evidence suggesting the ideal number of characters. Future investigations may tackle this issue.…”
Section: Sexualitymentioning
confidence: 99%
“…The advocated number for messages sent through SMS is 160. (22) For messages sent through WhatsApp, there is no evidence suggesting the ideal number of characters. Future investigations may tackle this issue.…”
Section: Sexualitymentioning
confidence: 99%
“…Lester et al (2010) found that patients using text messaging, through their mobile phones, linked to their antiretroviral therapy (ART) adherence, had significantly greater ART adherence rates and rates of viral suppression compared to patients not usign the text-messagingt service. In Kenya, Zurovac et al (2011) found the use of text messages to be efficient in the prevention and treatment of malaria. The use of social media platforms such as Twitter has also been found to be effective in health information dissemination (Scanfeld, Scanfeld & Larson, 2010).…”
Section: Reproductive Health Information Access Among Rural Women In mentioning
confidence: 99%
“…Improvement of patients' awareness about the need to confirm a malaria-free status after treatment might be achieved through the use of innovative approaches, such as mobile phone text messages with reminders to attend follow-up sessions. 70,71 Another metric worthy of increased attention during intensive malaria surveillance is the proportion of patients who need rescue therapy. These adaptations, together with new ways to document treatment successes, could form the basis of pragmatic early warning systems that allow further investigation.…”
Section: Early Warning and Investigationmentioning
confidence: 99%